2018
DOI: 10.1111/eea.12682
|View full text |Cite
|
Sign up to set email alerts
|

An objective high‐throughput screening method for thrips damage quantitation using Ilastik and ImageJ

Abstract: Quantifying thrips damage is challenging. We present an automated protocol for the screening of thrips (Thysanoptera: Thripidae) damage on Capsicum (pepper) leaves. We show that standardizing the exposed leaf side is important for resistance ranking of accessions. Our results indicate that thrips resistance is dependent on the plant's developmental stage and its genetic background. Ultimately, our method provides an efficient tool for screening for resistance to insects in applied research and commercial breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…This is why we fill the cages with 1% agarose the day before the experiment [23], and sandwich them between two glass plates as shown in Fig 1. Lastly, leaf disks are mechanically excised, thus wounding the tissues, especially along the border of the disk. As reported in [9], several studies found no differences between detached/attached leaves and leaf disc assays. The results obtained with leaf disks ought to be considered as a proxy precisely because of these limitations.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This is why we fill the cages with 1% agarose the day before the experiment [23], and sandwich them between two glass plates as shown in Fig 1. Lastly, leaf disks are mechanically excised, thus wounding the tissues, especially along the border of the disk. As reported in [9], several studies found no differences between detached/attached leaves and leaf disc assays. The results obtained with leaf disks ought to be considered as a proxy precisely because of these limitations.…”
Section: Discussionsupporting
confidence: 51%
“…Leaf-disk assays are commonly used to evaluate plant resistance against insects with chewing mouthparts [7,8] by measuring the area of tissues consumed. They can be used also on mites, thrips, aphids, whiteflies, or even fungi by monitoring visual changes related to the damaged areas of the leaves [9]. While disk assays have drawbacks such as the damage inflicted to the tissue, several studies demonstrate that resistance scores obtained using this approach are comparable to those completed on detached or attached leaves [9].…”
Section: Introductionmentioning
confidence: 99%
“…Per accession 8–10 plants were used for this choice experiment. Leaf disc experiments were performed as described by Visschers et al ( 2018a ). Briefly, using a cork borer, two leaf discs (1.5 cm diameter) were punched from each leaf, thereby avoiding the mid-vein.…”
Section: Methodsmentioning
confidence: 99%
“…Our results provide experimental evidence that leaf disc assays are a suitable method for screening resistance to thrips in Capsicum (Maharijaya et al, 2011;Visschers et al, 2018a). In longer-term whole plant screening assays, herbivore-induced defences may play a role when screening for resistance to insects (Dillon, Chludil, Reichelt, Mithöfer, & Zavala, 2018).…”
Section: Whole Plant Versus Leaf Disc Assaysmentioning
confidence: 66%